Droplets movement and deposition of an eight-rotor agricultural UAV in downwash flow field - Qing, Tang; Ruirui, Zhang; Liping, Chen; Min, Xu; Tongchuan, Yi; Bin, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The movement and deposition of the droplets sprayed by agricultural unmanned aerial vehicle (UAV) are influenced by the complex downwash flow field of the rotors. Instead of conducting field experiment, a high speed particle image velocimetry (PIV) method was used to measure the movement and deposition of the droplets at different rotating speeds of rotors (1000-3000 r/min) or at different transverse injecting points (20-50 cm away from its nearby rotors) in the downwash flow field of an agricultural UAV with eight rotors and conical nozzles. The maximum speed and size of the high speed zone of the droplets were found greatly influenced by the downwash velocity. The initial spray angle of the nozzle declined with the increase of downwash flow speed. It was found that the downwash velocity could not only change the deposition zone of the droplets, but also influence their distribution. The increase of the downwash velocity would increase the deposition uniformity of the droplets. The nozzle position in the downwash flow field could also influence the deposition of the droplets. When the transverse distance between the nozzle and its nearby rotors increased, the relative deposition near the downwash flow of the rotors increased simultaneously. However, the distance between the deposition peak and the nozzle stayed constant. The initial spray angle of the nozzle was not influenced by the transverse distance between the nozzle and its nearby rotors. The research results could provide a theoretical basis and reference for the optimization of the spray application of multi-rotor UAV to minimize droplets deposition uncertainty.Keywords: chemical spray, droplet deposition, UAV, flow field, multi-rotorDOI: 10.3965/j.ijabe.20171003.3075Citation: Tang Q, Zhang R R, Chen L P, Xu M, Yi T C, Zhang B. Droplets movement and deposition of an eight-rotor agricultural UAV in downwash flow field. Int J Agric & Biol Eng, 2017; 10(3): 47–56.